2013
DOI: 10.1159/000353510
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of a de novo 7q21.3q31.1 Deletion by CGH-SNP Arrays in a Girl with Multiple Congenital Anomalies Including Severe Glaucoma

Abstract: In this study, we present a female patient with a constitutional de novo deletion in 7q21.3q31.1 as determined by G-banding and CGH-SNP arrays. She exhibited, among other features, psychomotor retardation, congenital severe bilateral glaucoma, a cleft palate, and heart defect. Microarray assay disclosed a deleted 12.5-Mb region roughly 88 kb downstream the ectrodactyly critical region; thus, the patient's final karyotype was 46,XX.arr 7q21.3q31.1(96,742,140- 109,246,085)×1 dn. This girl represents the fourth p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Our patient's deletion does not include SHFM1 , DLX5 , or DLX6 , the major candidates for ectrodactyly associated with intermediate 7q deletion (OMIM 129900) [Scherer et al, ; van Silfhout et al, ; Martínez‐Jacobo et al, ]. Correspondingly, our patient does not have ectrodactyly of the hands or feet.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Our patient's deletion does not include SHFM1 , DLX5 , or DLX6 , the major candidates for ectrodactyly associated with intermediate 7q deletion (OMIM 129900) [Scherer et al, ; van Silfhout et al, ; Martínez‐Jacobo et al, ]. Correspondingly, our patient does not have ectrodactyly of the hands or feet.…”
Section: Discussionmentioning
confidence: 65%
“…1, Present Case; 2, Chen et al []; 3, Dirse et al []; 4, Al‐Hassnan et al []; 5, Uliana et al []; 6, Miller et al []; 7, Krepischi‐Santos et al []; 8, Martínez‐Jacobo et al []; 9, Rivera et al []; 10, Cheong et al []; 11, Ayraud et al []; 12, Morey and Higgins []; 13, Serup []; 14, Young et al [] (patient 5); 15, Dennis et al []; 16, Hull et al []; 17, Franceschini et al []; 18, Fagan et al [] (case 3); 19, Abuelo and Padre‐Mendoza []; 20, Manguoglu et al []; 21, Del Refugio Rivera‐Vega et al []; 22, Montgomery et al []; 23, Higginson et al []; 24, Klep‐de Pater et al [] (case 1); 25, Yilmaz et al []; 26, Kim et al []; 27, Zackowski et al []; 28, McElveen et al []; 29, Stallard and Juberg []; 30, Johnson et al []; 31, Pfeiffer []; 32, Valentine and Sergovich []; 33, Tajara et al []; 34, Chitayat et al [].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four CNVs were identified that overlapped or were close to transcription factors HES3 , TRIM71 , CUX1 and EIF4EBP2 which are important in cardiac development. HES3 and CUX1 have been reported to interact with Notch and Wnt pathways [ 22 , 23 ] and dysregulation of these signaling pathways is known to lead to congenital heart defects [ 24 , 25 ]. In case 1 a 22 Kb deletion was identified at 10q22.1, 19 Kb upstream of NODAL , which is a factor in cardiac progenitor differentiation [ 26 ] and an inducer of Sox17 , an endoderm-specific gene regulating paracrine signals in cardiogenesis [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Deletions and cnLOH mapped on 7q have been widely described in both hematological malignancies; specifically myelodysplastic syndrome, acute myeloid leukemia (AML) and splenic marginal zone lymphoma 14 15 16 ; and BC 17 18 . Furthermore, genomic deletions on chromosome 7q have also been associated with congenital defects, including developmental delay, learning difficulties, craniofacial dysmorphism and hypogenitalism 19 20 21 22 .…”
mentioning
confidence: 99%